PERLINDUNGAN HUKUM TEHADAP ANAK KORBAN INCEST DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Sandri Sandri; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One form of sexual crime that befalls children is incest, usually children areprosecuted. This case is one of the most extreme forms of child abuse, oftenresulting in serious and prolonged psychological trauma, especially by parents.known by other parties will feel ashamed. thus the need for further arrangementsregarding child protection in the future children come.The research objectives ofthis thesis are; First, determine the legality of legal protection for child victims ofincest in Indonesian laws and regulations.Second, to find out the form ofproviding legal protection to child victims of incest in the future. This type ofresearch is the writer of normative legal research or known as the legal researchof literature.From this research, the regulation of incest or better known as incestin the Indonesian Criminal Code is very important, especially regarding thesanctions. Incest cases are not ordinary rape cases, but also involve beliefs, thecontinuity of a family, the future of children, and the psychological conditions thatare formed. Therefore, it is very unfortunate if Indonesian law treats incestperpetrators the same as ordinary rape victims. There are two fundamentalproblems that can be First, in the law there is no definition of the victim'sbiological child. So does this have an impact on the equality of special treatmentfor children as victims both from their own families (biological children) andchildren outside the family, which is clearly different from the psychologicalimpact of a crime rape of the child of a rape victim (incest). Second, the law onthe protection of children is very clear, but its implementation has not beenrealized as expected. It is necessary to continuously amend the law and preparenew offenses, among others, with input from various scientific meetings whichalso means from various circles of society at large. Some results of research andstudies regarding the development of special offenses in society and developmentsin science and technology. Observation of new forms and dimensions of crime ininternational meetings or congresses and various kinds of internationalconventions both ratified and not ratified and results of comparative studies ofvarious Criminal Codes from sexual violence requires us to enforce and protect itin various prevention efforts, namely, social community approaches, earlychildhood sexual education, active socialization of the effects of incest, systems-based approaches and so on.Keywords: Incest – Child Protection - Victims – Sexual Violence